2019
DOI: 10.1074/jbc.ra119.009757
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C–dependent lysine demethylase 6 (KDM6)-mediated demethylation promotes a chromatin state that supports the endothelial-to-hematopoietic transition

Abstract: The authors declare that they have no conflicts of interest with the contents of this article. This article contains Figs. S1-S6 and Tables S1 and S2. The RNA-seq, ATAC-seq, and ChIP-seq data reported in this paper can be assessed under GEO GSE132970.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 48 publications
(52 reference statements)
4
40
0
1
Order By: Relevance
“…However, VC restored these abnormal epigenetic alterations in MC-LR-exposed oocytes. This confirmed that VC can act as an epigenetic regulator to enhance cell functions ( Zhang T. et al, 2019 ). Moreover, considering that changes in ATP levels correlate with the dysfunction of mitochondria present in MC-LR-exposed oocytes ( Yu et al, 2010 ), we concluded that disturbed cytoskeleton, abnormal epigenetics, and dysfunctional mitochondria were the reasons for the meiosis failure in MC-LR-exposed oocytes.…”
Section: Discussionsupporting
confidence: 65%
“…However, VC restored these abnormal epigenetic alterations in MC-LR-exposed oocytes. This confirmed that VC can act as an epigenetic regulator to enhance cell functions ( Zhang T. et al, 2019 ). Moreover, considering that changes in ATP levels correlate with the dysfunction of mitochondria present in MC-LR-exposed oocytes ( Yu et al, 2010 ), we concluded that disturbed cytoskeleton, abnormal epigenetics, and dysfunctional mitochondria were the reasons for the meiosis failure in MC-LR-exposed oocytes.…”
Section: Discussionsupporting
confidence: 65%
“…Given the therapeutic potential of blood and the immune cells such as NK and T cells, the generation of definitive multi-potent HSPCs in vitro, particularly from human PSCs has been a long-sought goal. However, HPCs derived from hPSCs have very limited potential in generating multiple blood lineages, particularly a very limited lymphoid potential 23,24,27,28 . During early hematopoietic development, the lymphoid lineages are mainly generated through definitive hematopoiesis [14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
“…In hPSC differentiation, hemogenic endothelial cells (HECs) express CD34 and CD31 and then show upregulated CD43 on the commitment of hematopoietic fate 22,[24][25][26] . CD43 has served as a marker to indicate hPSC-derived hematopoietic progenitors in many studies 23,24,27,28 . However, even though these CD43 + hPSC-derived HPCs could form various blood CFUs (colony-forming units), they have very limited definitive potency to give rise to immune cells 23,25 .…”
Section: Introductionmentioning
confidence: 99%
“…in vitro 91 high expression of TET3 may be in cell culture 53,92 a positive prognostic marker. 97 in vitro 71 correlated with adverse outcome in cell culture 70 in male AML patients. Mutations in KDM6A associated with cytarabine resistance.…”
Section: Context 1 Heterozygous Mutations In Tet2mentioning
confidence: 93%
“…Mutations in KDM6A associated with cytarabine resistance. 68 in cell culture 70,94 involved in the regulation of HSC self-renewal, knockout impairs self-renewal. 114 DNA demethylation, and 5hmC may be an epigenetic mark with its own reader.…”
Section: Context 1 Heterozygous Mutations In Tet2mentioning
confidence: 99%